Vitamin B6 in anxiety: sleep and immune function - Pertiwi, Lintang Mega; Fanani, Mohammad; Hikmayani, Nur Hafidha (Universitas Gadjah Mada, 2023)
Objective: This scoping review aims to explore the role of vitamin B6 in sleep duration and immune function in individuals with anxiety disorders. Methods: A search was conducted on scientific databases such as PubMed, Science Direct, and Google Scholar using the keywords